1974
DOI: 10.1111/j.1751-1097.1974.tb06561.x
|View full text |Cite
|
Sign up to set email alerts
|

The Dose Response Curve in Phytochrome‐mediated Anthocyanin Synthesis in the Mustard Seedling

Abstract: Abstract—The dose response curve for light (phytochrome)‐induced anthocyanin synthesis was determined in the mustard seedling. The curve gives the amount of anthocyanin (A) synthesized within 24 h as a function of the amount of Pfr* produced by a brief light pulse. The [Pfr] response curve is composed of two linear parts with very different slopes (a1,2) connected by a relatively narrow transient range (curved segment). The [Pfr] response curve extrapolates precisely through zero [Pfr]. The reciprocity law is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

1976
1976
2002
2002

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(26 citation statements)
references
References 21 publications
4
22
0
Order By: Relevance
“…This observation corroborates previous reports showing the activity of Arena phytochrome A in light-grown transgenic tomato seedlings (Boylan and Quail 1989), rice phytochrome A in transgenic lightgrown (Kay et al 1989) or etiolated (Nagatani et al 1991 tobacco seedlings, and Arena phytochrome A in lightgrown tobacco seedlings (Keller et al 1989). The degree of cotyledon unfolding plotted against calculated Pfr/P showed two linear segments, consistent with anthocyanin synthesis (Drumm and Mohr 1974) and glutamate synthase (Hecht and Mohr 1990) responses to Pfr, and equivalent to the biphasic fluence-response curves observed for seedling growth (Mandoli and Briggs 1981) and seed germination (Cone et al 1985), among other responses. The first segment, observed between calculated Pfr/P = 0 and ca.…”
Section: Discussionsupporting
confidence: 92%
“…This observation corroborates previous reports showing the activity of Arena phytochrome A in light-grown transgenic tomato seedlings (Boylan and Quail 1989), rice phytochrome A in transgenic lightgrown (Kay et al 1989) or etiolated (Nagatani et al 1991 tobacco seedlings, and Arena phytochrome A in lightgrown tobacco seedlings (Keller et al 1989). The degree of cotyledon unfolding plotted against calculated Pfr/P showed two linear segments, consistent with anthocyanin synthesis (Drumm and Mohr 1974) and glutamate synthase (Hecht and Mohr 1990) responses to Pfr, and equivalent to the biphasic fluence-response curves observed for seedling growth (Mandoli and Briggs 1981) and seed germination (Cone et al 1985), among other responses. The first segment, observed between calculated Pfr/P = 0 and ca.…”
Section: Discussionsupporting
confidence: 92%
“…pattern formation (Mohr, 1972). Previous studies of the formation of anthocyanin involved measurements of the total anthocyanin content of several pooled cotyledons and demonstrated the very precise control of the synthesis of anthocyanin by light and developmental state (Mohr, 1966;Drumm and Mohr, 1974;Steinitz et al, 1976). Approaches such as those described above cannot answer the question of how the spatial pattern is established at the cellular level.…”
Section: Introductionmentioning
confidence: 92%
“…Studies on photoregulation of anthocyanin biosynthesis have shown the connection between photoreceptor activation and anthocyanin accumulation (Mancinelli 1985;Mancinelli et al 1991). Although earlier studies were focussed mainly on the involvement of phytochrome (Siegelman and Hendricks 1957;Downs and Seigelman 1963;Drumm and Mohr 1974), there is also evidence for the involvement of the UV-A/blue light photoreceptor cryptochrome (Oelmuller and Mohr 1985;Sponga et al 1986;Hashimoto et al 1991). However, various photomorphogenic mutants of tomato point to a key role of phytochromes in the photoregulation of anthocyanin synthesis (Adamse et al 1989).…”
Section: Introductionmentioning
confidence: 95%